Visual Identity “Licincyin” As A Promotional Strategy For Processed Eel Home Industrial Products - Qurrotul A.FS, Nurul Izza; Yunianto, Ipung Kurniawan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2019)
Society must begin to adapt to the new way of life, often referred to as the 'new normal life.' This transitional period has led to significant changes in societal behavior. One of these changes is the shift in food consumption patterns. With the increased demand, the market segment predictions and the scope of frozen food producers are expected to expand further.Frozen smoked eel processing products in Indonesia are not the only ones, but there are still very few business actors. This is a great opportunity for the "Licincyin" home industry to promote their products. This research aims to design a visual identity for Licincyin with an image of Indonesian culture as a visual attraction as a means of branding and product communication for potential consumers. This research uses qualitative methods in the form of interviews, documentation, and literature study, while the visual design in this research uses design thinking methods, SWOT analysis, and Hiroyoshi Tsukamoto's Manga Matrix approach to examine the characters/mascots on Licincyin product packaging. The results of this research are Licincyin's visual identity in the form of logo designs, packaging, mascots and visual elements in packaging with images of Indonesian culture